The Effect Of The Basic Education Teacher Diploma Training Programme (BETD) On Teachers' Productivity In Caprivi Region, Namibia [LB1727.N3 S193 2008 f rb]. - Samupwa, Austin Machana (2008)
Kajian ini bertujuan untuk mengenal pasti kesan program latihan pendidikan asas diploma perguruan di Negeri Caprivi, Naimibia ke atas produktivti guru.